Introducing Maya 7 : - Derakhshani, Dariush (Wiley Pub., 2006)
Enter a New Dimension: Get a solid grasp of the core Maya and 3D concepts; Learn to navigate the Maya 7 interface; Experiment with Maya modeling by creating a hand, an axe, and a locomotive; Explore the basics of NURBS, polygons, and subdivision surfaces; Discover the nuances of shading and texturing; Try your hand at animation; Rig a locomotive model for automated animation; Get a feel for Maya lighting, rendering, and dynamics; Find out how to use Maya and Photoshop in unison to texture your scene